Sustainable development and mega infrastructure: an overview of the issues. Issue 1 (2nd January 2019) - Sturup, Sophie; Low, Nicholas
Abstract: Sustainable development is a concept which has only recently been applied to the analysis of infrastructure megaprojects. Yet new built infrastructure has a crucial role to play in both the continued and future development of communities, societies and ultimately the world economy and global ecosystem. This paper discusses the meaning of 'sustainable development' and 'sustainability' in terms understood from its origins in the relationship between economic development and the conservation of the natural world. While the definition of sustainability has perhaps moved beyond its origins, it remains the case that no condition of sustainability can be conceived without bringing our relationship to the natural world into balance, and thus we work from this perspective from which we explore some of the ways sustainability might be applied to megaprojects. In so doing, we hope to open a discussion to which future contributions to this journal can contribute.